The marriage gap: Optimal aging and death in partnerships - Johannes Schünemann; Holger Strulik; Timo Trimborn (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2017)
Married people live longer than singles but how much of the longevity differential is causal and what the particular mechanisms are is not fully understood. In this paper we propose a new approach, based on counterfactual computational experiments, in order to asses how much of the marriage gap can be explained by public-goods sharing and collective bargaining of partners with different preferences and biology. For that purpose we integrate cooperative decision making of a couple into a biologically-founded life-cycle model of health deficit accumulation and endogenous longevity. We calibrate the model with U.S. data and perform the counterfactual experiment of preventing the partnership. We elaborate three economic channels and find that, as singles, men live 8.5 months shorter and women 6 months longer. We conclude that about 30% of the marriage gain in longevity of men can be motivated by economic calculus while the marriage gain for women observed in the data is attributed to selection or other (non-standard economic) motives.
Keywords: D91; J17; J26; I12; 330; health; aging; longevity; marriage-gap; gender-specific preferences; unhealthy behavior